The Economics of Cooking Energy Scenario in Arid Rajasthan - Ram, K Anantha; Bhati, G N; Goyal, Daulat (Annals of Arid Zone, 2016)
The analysis of non-commercial fuel supply and its use on randomly selectedfarms in arid Rajasthan revealed that about 60 per cent of fuel wood consumedon sample households was supplied by ones own farm. Fuelwood, dungcakeand crop wastes accounted for 58,28 and 14 per cent of total noncommercialfuels used in cooking food. The per household annual consumptionof non-commercial fuels ranged between 3. 13 to 5.62 t in different size offarms. However. the actual per capita energy derived from the non-commercialfuels consumed on sample farms was short by 22 per cent compared torequirement in country side conditions. It is inferred that the fuels are usedinefficiently leading to diversion of valuable cowdung to hearths. The perfarm cowdung used as fuel worth Rs. 108.00 was actually worth Rs. 302.00 interms of nutrients (NPK) contained in it.